(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
The paper is devoted to the study of the stress-strain state (SSS) of reinforced concrete composite-reinforced double-layer combined slabs. The derivation of equations and formulation of boundary conditions are given, taking into account the interlayer shear and the compliance of the adhesive joint. The analysis of the influence of the geometric and physical parameters of double-layer combined slabs on the SSS is presented.